Nuss procedure for repair of pectus excavatum after failed Ravitch procedure in adults: indications and caveats - Kocher, Gregor J.; Gstrein, Nathalie; Jaroszewski, Dawn E.; Ewais, Mennatallah M.; Schmid, Ralph A. (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: Recurrence of pectus excavatum (PE) is not an uncommon problem after open repair using the Ravitch technique. The optimal approach for redo surgery is still under debate, especially in adults with less chest wall pliability. Aim of this study was to investigate the usefulness and efficacy of the minimally invasive Nuss technique for repair of recurrent PE after conventional open repair. Methods: We performed a retrospective multicentre review of 20 adult patients from University Hospital Bern (n=6) and the US Mayo Clinic (n=14) who underwent minimally invasive repair of recurrent PE after unsuccessful prior Ravitch procedure. Results: Mean patient age at primary open correction was 21 years, with recurrence being evident after a mean duration of 10.5 years (range, 0.25–47 years). Mean age at redo surgery using the Nuss technique was 31 years, with a mean Haller index of 4.7 before and 2.5 after final correction. Main reason for redo surgery was recurrent or persistent deformity (100%), followed by chest pain (75%) and exercise intolerance (75%). No major intraoperative or postoperative complications occurred and successful correction was possible in all patients. Conclusions: Although the procedure itself is more challenging, the minimally invasive Nuss technique can be safely and successfully used for repair of recurrent PE after failed open surgery. In our series final results were good to excellent in the majority of patients without major complications or recurrence.